Depositional evolution of a tectonically‐confined proximal‐foredeep deep‐marine system: Miocene Serra Palazzo Formation (Southern Apennines, Italy). (10th August 2021) - Cerone, Davide; Gallicchio, Salvatore; Patacci, Marco
Abstract : The Miocene Serra Palazzo Formation (SPF) was deposited in a foredeep basin in front of the growing Southern Apennines orogenic wedge. A new detailed facies analysis, based on high‐resolution physical stratigraphy, for a 570 m‐thick interval, has been undertaken in order to reconstruct the depositional history. Two phases of development can be recognized. The older one was characterized by the sedimentation of sandy channel‐lobe transition zone (cltz) deposits with various degrees of amalgamation; roughly in the middle, a 26 m‐thick sandy megaturbidite was deposited. At this time, basin topography, including the inbound slope base and topography due to the orogen‐related flexural subsidence, caused significant flow confinement illustrated by a number of sedimentary features, such as syn‐sedimentary deformation structures, hummocky laminations, and differences in the palaeocurrent directions recorded in the same event bed. The younger phase was characterized by the sedimentation of more‐proximal amalgamated sandy channel deposits, followed upwards by an even more‐proximal sequence of thick levees with thin‐bedded and fine‐grained facies. Tectonics was one of the main controls on the stacking patterns of the submarine fans of the SPF basin. Particularly, the outward thrust migration governed the evolution from the cltz deposits to the levee deposits and it might have caused the repeated waxing‐waning flow cycles recorded in the channel deposits and the changes in bed dip angles in the levee deposits. Abstract : Detailed facies analysis and depositional history of the Serra Palazzo Formation, a Miocene foredeep deep‐marine system of the Southern Apennines (Italy), are presented. The key role of active tectonics and basin topography in controlling the deposition of this system is discussed.